Communication Styles, Care- Seeking and Preventive Behaviors in COVID-19 Patients in Northwest of Iran - Asghar Tanomand; Hossein Safari; Sedigheh Salavati; Ali Soleimani; Arman Latifi (Shiraz University of Medical Sciences, 2023)
Background: The most important way to prevent COVID-19 is to observe health behaviors such as keeping social distance from one another. After getting COVID-19, care-seeking behaviors can affect the severity of the disease. The current study aimed to investigate and compare the communication styles, care-seeking, and health behaviors in patients with COVID-19.Methods: A cross-sectional study was performed using a selfadministered questionnaire on patients with COVID-19 in Maragheh in 2020. The study population included 450 people selected using simple random sampling. Chi-square, one-way ANOVA, and Pearson Product Moment Correlation tests were used to compare communication styles, care-seeking, and health behaviors among outpatients and inpatients with COVID-19. Data were analyzed using SPSS 23 software.Results: The first place to seek t reatment for outpatients and inpatients with COVID-19 was health centers (28.2%) and hospitals (44.5%), respectively. In terms of communication behaviors, close contact of family members with others at work, getting the disease from close friends or colleagues (45.8%), and having a history of contact with an infected COVID-19 person (43.5%) were the most reported items by outpatients. On the other hand, hospitalized cases reported close contact of family members with others at work (62.4%), attending physicians' offices (43.8%), and attending gatherings (41.2%) more than other communication behaviors (P<0.0001).Conclusion: Care-seeking behavior is more appropriate among outpatients than inpatients, and preventive behaviors are more stable in outpatients than inpatients. Therefore, health education interventions in the community should focus on correcting careseeking behaviors and promoting good social communications.